Pengendalian Persediaan Bahan Baku Untuk Lemari Tipe Sliding Door Glass (Studi Kasus di PT Alba Unggul Metal) - Hartono, Hartono; Pramuji, Dwi (Journal Industrial Manufacturing, 2024)
PT Alba Unggul Metal faced several operational problems in its production activities. In this study, the focus is on standard products owned by PT Alba Unggul Metal, especially SDG type cabinets, due to delays in delivery schedules caused by scarcity of raw materials, most are SDG type cabinets. The purpose of this study was to plan the raw material requirements for SDG type cabinets so that there is no scarcity of raw materials in the warehouse. The method used is the Economic Order Quantity method, the Period Order Quantity method and the Min-Max method. After analysis and discussion, it is known that the Economic Order Quantity method is the most optimal method compared to the Period Order Quantity method and the Min-Max method. Then the Company can better control inventory and delivery time of raw materials by using the EOQ method. As an example of the calculation for an SD SPCC plate measuring 0.7mm x 2440mm x 1220mm with an optimal order quantity of 512 pieces for one order, 157 safety stocks, reorder point when stock is 493 sheets, and order frequency 24 times a year. After implementation and data sampling for three months in April, May and June 2023 there was no shortage of raw materials which caused a delay in the delivery schedule for SDG type cabinets.Keywords : Inventory control, Economic Order Quantity, Period Order Quantity, Min-Max, Reorder Point, Safety Stock.